(untitled) (Indian Journal of Veterinary Pathology, 2025)
Ducklings (aged 45-50 days) from a nomadic flock had mortalities of 4-5 birds per day since one week was reported. Systematic postmortem was conducted. Samples were collected for histopathological, microbiological and parasitological studies. Gross examination revealed thin whitish membranous deposits over the pericardium and liver. Pericardium was tightly adhered with the heart. Caecum was slightly distended and showed multifocal, firm creamy yellowish-white adherent foci over the mucosa. Microscopically, chronic fibrino-purulent pericarditis, epicarditis, fibrinous perihepatitis, diptheritic typhlitis with trophozoites of Histomonas meleagridis was observed. Histomonas meleagridis was confirmed by parasitological examination. Escherichia coli was isolated from heart blood and liver swabs. Histomonads exacerbate the illness when concurrent infection with pathogenic bacteria prevails. The present study described the co-infection of histomoniasis and colibacillosis in ducklings under natural condition.